Tangled Roots and Murky Waters: Piecing Together Panama’s Mangrove Policy Puzzle - Chamberland-Fontaine, Sarah; Heckadon-Moreno, Stanley; Hickey, Gordon M. (Frontiers in Forests and Global Change, 2022)
Mangrove forest policies are often characterized by their fragmented nature, as multiple sectors, disciplines, and institutional structures interact to affect mangrove conservation and management. This study analyzes mangrove forest policies in Panama, a country known for its rich mangrove coverage and, conversely, its high rates of mangrove loss, urban expansion, and coastal development. To complement the policy analysis, key informant interviews with national policy actors are used to gather insights on policy implementation challenges and potential multi-actor collaboration opportunities. Results suggest that despite the development of multiple policies targeting wetlands and conferring a high conservation status to mangroves in Panama, mangrove protection is challenged by competing governmental agendas and policy implementation gaps. Efforts to strengthen mangrove conservation and initiate participatory management processes were also found to conflict with institutional structures that struggle to include local communities and foster collective action.